2020
DOI: 10.3390/land9070212
|View full text |Cite
|
Sign up to set email alerts
|

From Closed to Claimed Spaces for Participation: Contestation in Urban Redevelopment Induced-Displacements and Resettlement in Kigali, Rwanda

Abstract: In many cities and urban areas in Africa, land acquisition for urban redevelopment, land readjustment, and resettlement of affected urban residents are currently framed as innovative approaches to eradicating informal settlements, improving the living environments, and supporting the implementation of newly adopted city Master Plans. Nevertheless, it is not yet known how the responses of institutions and affected people shape these processes. Based on research conducted in Kigali, Rwanda, this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…The Master Plan 2013 introduced zoning, and thus regulated the means of land use, the heights of buildings and permissible densities of population in each area. A further assumption is that people living in hazardous areas will be resettled [75,81], and this may be a serious matter for the most vulnerable groups, with such negative socioeconomic consequences as loss of means of upkeep and reduced food security, the severing of social ties, marginalization, or even induced homelessness [82,83]. Resettlements therefore lead to the exclusion of the most vulnerable city residents, which is in contradiction with the concepts of smart, resilient and soft cities that comprise solutions aimed at social inclusion.…”
Section: Spatial Planning and Urban Agriculture Managementmentioning
confidence: 99%
“…The Master Plan 2013 introduced zoning, and thus regulated the means of land use, the heights of buildings and permissible densities of population in each area. A further assumption is that people living in hazardous areas will be resettled [75,81], and this may be a serious matter for the most vulnerable groups, with such negative socioeconomic consequences as loss of means of upkeep and reduced food security, the severing of social ties, marginalization, or even induced homelessness [82,83]. Resettlements therefore lead to the exclusion of the most vulnerable city residents, which is in contradiction with the concepts of smart, resilient and soft cities that comprise solutions aimed at social inclusion.…”
Section: Spatial Planning and Urban Agriculture Managementmentioning
confidence: 99%
“…However, in relation with the broken social ties and cultural practices, this policies are deaf and dumb to meet the intangible losses. It's a stunning fact from many of the studies and experiences that the loss of social capital and social cohesion is common in redevelopment displacement (Nikuze, Sliuzas, & Flacke, 2020).…”
Section: Literature Review: Concepts Of Urban Redevelopment and Social Capitalmentioning
confidence: 99%
“…Another survey conducted in Guangzhou, China showed that those who moved back to their previous neighborhoods after redevelopment suffered from a sense of disorientation and isolation (Yuqi Liu et al, 2017). Moreover, the detrimental effect of urban redevelopment appears to vary among different social groups in low-income neighborhoods; after the large-scale redevelopment, resettled residents are more likely than newly arrived residents to be subject to social disturbance (Nikuze et al, 2020). While resettled residents tend to have little contact with new residents as they still rely on former neighborly relations for social support, new residents rarely seek social support through either current or former neighborly relationships (Ambaye & Abeliene, 2015).…”
Section: Literature Review: Concepts Of Urban Redevelopment and Social Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Rwanda's economic reform associated with its market-led model of economy refers to structural transformation, mostly away from subsistence agriculture and towards poverty reduction [1]. The expropriation risk for public interest is a recurrent concern of the urban population in Kigali, a city of Rwanda [2,3]. However, the phenomenon is also present in rural areas.…”
Section: Introductionmentioning
confidence: 99%